REIMAGINING THE FEMININE VOICE: ANALYZING WOMEN’S AGENCY IN LITERATURE WITH SPECIAL REFERENCE TO ARUNDHATI ROY AND VIRGINIA WOOLF - Dharshini, Meena Priya; Moorthi, S (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This paper is devoted to the transformation of female voices and power in the art of Virginia Woolf and Arundhati Roy, paying attention to their different but complementary contributions to English literature. Woolf, who is the first modernist female author, dismantles the mechanisms of male domination and argues for the intellectual and financial autonomy of women, as in A Room of One's Own. Roy, in her postcolonial magnum opus The God of Small Things, explores the socio-political space of India to give a portrayal of the women whose voices are suppressed and the subversive ones. This analysis, by comparing Woolf’s 20th-century demand for the inclusion of women in the literary field with Roy’s 20th-century questioning of gender, caste, and colonial heritage, shows how women’s voices in English literature have changed over time. Using feminist and postcolonial approaches, the work brings out the authors' ways of restructuring subjectivity through the narrative form, the use of language, and resistance. At the same time, the paper shows that Woolf and Roy create connections across time and culture as they see new possibilities for gender egalitarianism and literary representation.